Preparation of Methyl Acrylate-Grafted Oil Palm Empty Fruit Bunch Fiber and its Application as a Filler in Poly(Vinyl Chloride)/Epoxidised Natural Rubber Composites - Raju, Gunasunderi (2005)
Graft copolymerization of methyl acrylate (MA) onto OPEFB fiber has been successfully carried out using hydrogen peroxide and ferrous ammonium sulfate as initiators in an aqueous medium. The effects of reaction temperature, reaction period and amount of monomer and initiators on the percentage of grafting were investigated. The results show that the percentage of grafting depends on reaction period and temperature as weil as concentration of monomers and initiators. The maximum percentage of grafting was obtained when the reaction was carried out using 33.36 mmol of MA, 6.00 mmol of H202a nd 0.191 mmol of ~ efo~r 21+0 minutes at 75OC. The presence of the functional group in the grafted polymers was characterized by FTIR spectroscopy. Scanning electron microscopy was used to study the surface morphology. Thermogravimetric analysis indicated that the grafted OPEFB is thermally stable than the virgin OPEFB. Effect of oil palm empty fruit bunch (OPEFB) fiber and poly(methy1 acrylate) grafted OPEFB Gn several mechanical properties of poly(viny1 ch1oride)lepoxidized natural rubber (PVCENR) 50150 and 70130 blends were also studied. The composites were prepared by mixing the fiber and the PVCJENR blend using HAKEE Rheomixer at the rotor speed of 50 rpm, mixing temperature 150°C and mixing period of 20 minutes. The fiber loadings were varied from 0 to 30% and the effect of fiber content in the composites on their tensile strength (Ts), Young's Modulus, Modulus at 100% (Mloo), elongation at break (Eb), flexural modulus, hardness and impact strength were determined. An increasing trend was observed in the tensile strength, Young's Modulus, flexural modulus, impact and hardness with the addition of grafted and ungrafted fiber to the PVCIENR blend. A higher elongation at break and tensile strength and decrease in the flexural and Young's modulus observed with the addition of PMA-g-OPEFB fiber compared to ungrafied fiber. This observation indicates that grafting of PMA onto OPEFB impart some flexibility to the blend. Scanning electron microscope confirms that the increase in properties is caused by improved fiber-matrix adhesion. There was less inclination for the fibers to pull out of the matrix. Furthermore the thermal analysis by Dynamic Mechanical Analysis (DMA) indicated shifting in the Tg of the PVCJENR composites with the addition of the OPEFB fiber. Thermogravemetric analysis (TGA) did not show any significant changes in the thermal stability. FTIR spectrums for the grafted and ungrafted fiber composites were almost identical. Effect of electron beam radiation on the tensile properties of the PVCJENR composites with 10% of fiber loading was studied. Electron beam irradiation and addition of crosslinking agent cause enhancement in tensile strength, Young's Modulus, Modulus at 100% (Mloo)a nd gel content, with a concurrent reduction in the elongation at break (Eb) of the PVCIENR composite